Occurrence of abnormal tapeworms: finding of triradiate Taenia multiceps - Gomez-Puerta, Luis A. (2022)
Three atypical cestodes with abnormal morphology were found in a domestic dog. The cestodes had a scolex with six suction cups and a triradiate strobila. All parasites were gravid cestodes. In addition, the dog was infested with 324 normal cestodes. Both cestodes (normal and abnormal) were morphologically and molecularly identified as Taenia multiceps. The sequences of the cytochrome c oxidase subunit 1 gene of the triradiate cestode and normal cestodes were identical to each other and had more than 99% similarity with other published and recorded sequences for T. multiceps. These findings represent the first record of atypical cestodes and massive cestode infestation by T. multiceps in a dog from Peru.